FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Istifaroh, Anisya; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine some factors which influence the corporate social responsibility disclosure of manufacturing companies which are listed in Indonesia Stock Exchange (IDX) and PROPER of the ministry of Environmental in 2011-2015. Some factors which are used in this research are profitability, leverage, board of commissioner size and environmental performance. The dependent variable which is used in this research is corporate social responsibility disclosure. The population of this research is 67 manufacturing companies which are listed in Indonesia Stock Exchange and PROPER of the ministry of Environmental in 2011-2015 periods. The sample collection technique has been done by using purposive sampling and 18 companies which have met the research criteria have been selected as samples. The analysis method has been carried out by using multiple linear regressions. The analysis method has been carried out by using multiple linear regressions analysis with the instrument of SPSS 23 version for windows. The result of this research shows that profitability has positive influence to the corporate social responsibility disclosure, leverage has positive influence to the corporate social responsibility disclosure, board of commissioner size has positive influence to the corporate social responsibility disclosure and environmental performance has positive influence to the corporate social responsibility disclosure.Keywords: Profitability, leverage, board of commissioner size, environmental performance, corporate social responsibility disclosure.